DOI: 10.4995/thesis/10251/12127
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Fully-Automatic and Interactive Phrase-Based Statistical Machine Translation

Abstract: ACKNOWLEDGEMENTSHan transcurrido ya varios años desde que uno de mis codirectores de tesis, Ismael, me hablara por primera vez sobre la traducción automática estadística en su despacho de la Escuela Politécnica Superior de Albacete. La historia de esta tesis en cierta forma arranca ese día y se ha prolongado, al menos, hasta el momento de escribir estas líneas.Durante todo ese tiempo, es mucha la gente que de un modo u otro ha influído en este trabajo. Quisiera dar las gracias en primer lugar a mis directores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 122 publications
0
13
0
Order By: Relevance
“…The results of user trials (Macklovitch, 2006) showed gains in productivity (measured in number of words translated per hour) of around 15-20%. A number of projects (Koehn, 2009;Ortiz-Martínez, 2011;Alabau et al, 2010Alabau et al, , 2013 have recently continued the research where TransType2 left it off. As regards tools, both Caitra (Koehn, 2009) and the CASMACAT Workbench (Alabau et al, 2013) are web applications with an underlying SMT-based ITP system.…”
Section: Related Workmentioning
confidence: 99%
“…The results of user trials (Macklovitch, 2006) showed gains in productivity (measured in number of words translated per hour) of around 15-20%. A number of projects (Koehn, 2009;Ortiz-Martínez, 2011;Alabau et al, 2010Alabau et al, , 2013 have recently continued the research where TransType2 left it off. As regards tools, both Caitra (Koehn, 2009) and the CASMACAT Workbench (Alabau et al, 2013) are web applications with an underlying SMT-based ITP system.…”
Section: Related Workmentioning
confidence: 99%
“…For this purpose, a log-linear SMT model where all its score components are incrementally updateable is defined. The implemented proposal uses the incremental version of the EM algorithm (Neal and Hinton, 1998) and the specific details can be found in (Ortiz-Martínez et al, 2010;Ortiz-Martínez, 2011). Empirical results obtained with THOT and reported in (Ortiz-Martínez et al, 2010;OrtizMartínez, 2011) show that incremental learning allows to significantly reduce the user effort in IMT tasks with respect to that required by a conventional IMT system.…”
Section: Incremental Learning For Smtmentioning
confidence: 99%
“…Such a formalisation was introduced in (Ortiz-Martínez, 2011) and it generates the suffixes required in IMT by partially aligning a prefix of the target hypotheses with the user prefix. Once the partial alignment is determined, the suffix is given by the unaligned portion of the target sentence.…”
Section: Interactive Machine Translationmentioning
confidence: 99%
“…If the user feedback leads to a specific state in the word graph that has no path to any final state, the system fails. An error correction method is used to overcome this issue (Barrachina et al, 2009;Ortiz-Martínez, 2011), but it may lead to successive wrong hypotheses. NMT systems handle the out-of-vocabulary problem by applying splitting unknown words, using BPE.…”
Section: Prefix-based Interactionmentioning
confidence: 99%